Capital structure (debt policy) on company performance : study on SME company in Malaysia / Nurul Nadia Mohd Apandi - Mohd Apandi, Nurul Nadia (Faculty of Business Management, 2017)
Determining right financial policies in order to ensure the sustainability of company is a part of vital aspects in company decision. Implementing debt policy or debt structure is considered as crucial factor to the company’s value. This research is conduct to study about relationship of debt structure and company performance of Small Medium Enterprise in Malaysia. Using panel data of a company in Malaysia and adopting the regression model the study will run on this topic. In this research, company performance indicators are considered as Return on Assets (ROA), and Debt Ratios (Current Debt, Non-Current Debt,Total Debt and Trade Credit Ratio).